Social transfers and reduction of developmental disparities with reference to the situation in the Republic of Macedonia - Pejkovski, Jovan (Ревија за социјална политика/Journal of Social Policy, 2013)
The existence of a developmental lag and economic and social inequalities in the society raises the question of how to reduce them and which forms and redistribution policies of created values should be set to influence mainly persons at risk. Understandings of social transfers as unproductive and restricted for growth as a result of diverting of funds in a national economy are increasingly being replaced by assessments of their necessity and they are seen as a requirement for their strong influence in social relations. Social transfers and social stability are inter-dependentand, inter-related, together with economic growth dynamism and development. The paper analyzes the issue of social transfers, which is becoming an important part of the macroeconomic policy of each country. The paper also analyzes different perceptions of the increase and reduction of social transfers depending on the position of the entities that affect policy making .Transfers that occur in the system of pension insurance and the impact on the families in Macedonia where pensions are the only income, entails the need to consider this segment and its directions in terms of the aging population. Specific indicators for certain categories of citizens, make us understand the challenges that they face daily, as well as perceive sustainability and/or limitations that affect the feasibility of development and the opportunities for change of the objectives of social policy. Finally the paper concludes with remarks on the sensitivity of social transfers, especially in conditions of recession pointing out to their importance in particular for the protection of parts of the population and in overcoming poverty and social exclusion. The paper also points to the need for the scope of social transfers to be compared in terms of the impact of income of certain categories, the amount of social benefits and the sustainability of the individual and family in market conditions. This allows on the macro level to track prevailing policies that affect beneficiaries of such transfers, as well as to propose changes to the system of fund transfers.